2020
DOI: 10.21037/tcr.2019.12.08
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of osteopontin expression, Ki67 index and prognosis in squamous cell carcinoma and cysts of the oral cavity

Abstract: Background: Recent studies have shown a strong relationship between the expression of osteopontin and oral carcinogenesis. Osteopontin (OPN) has been shown to play a major role in regulating the aggressiveness of cancer cells and promote tumor growth. Odontogenic cysts are an essential aspect of oral and maxillofacial pathology. They are relatively frequent lesions with different clinical behavior. Some of them may have a proliferative pattern of growth and neoplastic nature. Evaluation of osteopontin expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…In full agreement with our findings, Kechik and Siar [31] results showed under-expression and indistinctive distribution patterns of OPN among all studied samples of three types of cysts RCs, DCs and OKCs. Similarly, our observations of OPN concurred with the findings of existing studies of Salehinejad et al [32] and Woźniak et al [33] who reported absent or weak expression of this antibody in RCs and DCs. This was clarified by that OPN could be well expressed in non-malignant tissues because of its multiple physiological activities.…”
Section: Discussionsupporting
confidence: 93%
“…In full agreement with our findings, Kechik and Siar [31] results showed under-expression and indistinctive distribution patterns of OPN among all studied samples of three types of cysts RCs, DCs and OKCs. Similarly, our observations of OPN concurred with the findings of existing studies of Salehinejad et al [32] and Woźniak et al [33] who reported absent or weak expression of this antibody in RCs and DCs. This was clarified by that OPN could be well expressed in non-malignant tissues because of its multiple physiological activities.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with most of the reviewed authors. 1 However, Ingale et al 29 found a significant higher expression of Osteopontin in HNSCC patients above 51 years of age. Osteopontin expression was significantly high in ulcerative pattern, lymphovasular invasion and extracapscular extension.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, the primary role of Osteopontin immunoreactivity in tumor progression and an increased risk of metastasis have already been considered. 1 Luo et al 36 demonstrated a positive correlation between Osteopontin immunoreaction and unfavorable overall survival rates. These results were in agreement with ours as we observed significant shorter DFS in high expression of Osteopontin (mean DFS 18.7 ± 1.6 mo vs. 35 ± 0.6 in the negative expression group) and inferior overall survival among the same group as well.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations